Indonesian Economic Transformation and Employment : Policy Input for an Indonesia Jobs Strategy - World Bank Group (World Bank, Washington, DC, 2016)
The current downturn in commodity prices provides an opportunity for Indonesia to shift away from its dependence on commodity-driven growth towards higher value-added activities in manufacturing and services. However, Indonesia faces both global and structural challenges in making this transition. Global challenges include competition from regional trade agreements, especially the TPP, but also from structurally lower global trade growth. In addition, Indonesia’s manufacturing sectors have also been losing competitiveness to regional competitors, while most job creation in the 2000s took place in low productivity sectors. This report aims to show the patterns of economic transformation in Indonesia in the past decade and a half, especially in terms of jobs and employment. The report highlights barriers to labor movement and macroeconomic sources of demand for labor. The report seeks to contribute to the design of a jobs strategy that emphasizes the transition of workers from low to high productivity sectors. While Indonesia has, so far, relied on job creation in low-productivity, and even vulnerable, employment, future challenges would require the country to shift to higher productivity and quality jobs.